Empowerment Of The Empowerment of the Rohis Program as an Internalization of Islamic Propagation at SMPN 11 Pekanbaru City, Riau: Empowerment of the Rohis Program as an Internalization of Islamic Propagation at SMPN 11 Pekanbaru City, Riau - Ida Wati; Cutra Aslinda; Fitri Almaidah; Sherena Mia Adelina Lubis (LPPM Universitas Putera Batam, 2026)
Islamic Propagation Through da'wah activities is basically an activity carried out openly to make every human being aware of doing good and prohibiting actions that are prohibited in Islamic teachings. Islamic Spiritual Activities (ROHIS) Schools are a reflection of religious activities in public schools. Community Service Activities aim to provide assistance to School Rohis in the form of Empowerment of Rohis Programs as Internalization of Islamic Propagation. The activity lasted for approximately 3 hours by providing assistance with Rohis material to become a Role model in Islamic propagation, building Islamic communication media in da'wah activities at school, the activity was held in the Multimedia room of SMPN 11 Pekanbaru City, Riau, which was attended by 35 students who were members of the Osis organization , and Rohis , the activity took place enthusiastically, all participants were active in the mentoring activities. The results of the PKM activity, SMPN 11 students can implement material in religious da'wah based on Islamic teachings, as well as create a religious school environment, Islamic propagation can be integrated into conventional and digital da'wah activities in the school environment.